An analysis of shari'ah audit practices in Islamic banks in Malaysia - Nur Laili binti Ab Ghani (Institute of Islamic Banking and Finance (IIBF), International Islamic University Malaysia, 2014)
Shari'ah audit is an important element to ensure Shari'ah compliance in Islamic banking operations. Currently in Malaysia, each Islamic bank and financial institution is required by the Shari'ah Governance Framework to establish the Shari'ah audit function to provide reasonable assurance and ensure an effective internal control system for Shari'ah compliance. At the moment, there is lack of empirical studies conducted to ensure proper practice of the Shari'ah audit in Islamic banks in the absence of a Shari'ah audit framework. The primary objective of this research is to determine the extent of Shari'ah audit practices in Islamic banks in Malaysia. The study also evaluates the supervisory and practical challenges in the implementation of Shari'ah audit practices. The research adopts the mixed method approach consisting of a survey questionnaire and structured interviews. Survey questionnaires were distributed to the heads of Shari'ah audit, internal Shari'ah auditors, Shari'ah executives and Shari'ah Committee members of 16 Islamic banks in Malaysia. The study conducts structured interviews with the Shari'ah Committee members in selected Islamic banks. The study adopts the Exposure Draft of Internal Shari'ah Audit Framework (ISAF) issued by the International Shari'ah Research Academy (ISRA) as a benchmark to measure the extent of Shari'ah audit practices. From the findings, the results indicate that almost all Islamic banks have established the audit objectives, governance structure, competency of internal Shari'ah auditors, audit process and reporting requirements as part of their Shari'ah audit practices. However, some Islamic subsidiaries have excluded audit scope and audit charter. Also, internal Shari'ah auditors, Shari'ah executives and Shari'ah Committee members agreed that it is important to develop a proper structure for the Shari'ah audit function in Islamic banks. The study found that Shari'ah Committee members understand Shari'ah audit in terms of ensuring Shari'ah compliance, the need to ensure competency of internal Shari'ah auditors and the need to have audit guidelines. They also faced challenges such as to supervise Shari'ah audit findings, to determine Shari'ah audit work and to conduct an internal Shari'ah audit. In conclusion, the good Shari'ah audit practices in Islamic banks have constituted a positive development in enhancing the integrity of Islamic banks. This further highlights the need for Bank Negara Malaysia to establish a standard Shari'ah audit framework in Malaysia.